6(x-4)=40

Simple and best practice solution for 6(x-4)=40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-4)=40 equation:


Simplifying
6(x + -4) = 40

Reorder the terms:
6(-4 + x) = 40
(-4 * 6 + x * 6) = 40
(-24 + 6x) = 40

Solving
-24 + 6x = 40

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '24' to each side of the equation.
-24 + 24 + 6x = 40 + 24

Combine like terms: -24 + 24 = 0
0 + 6x = 40 + 24
6x = 40 + 24

Combine like terms: 40 + 24 = 64
6x = 64

Divide each side by '6'.
x = 10.66666667

Simplifying
x = 10.66666667

See similar equations:

| -2a+13/5=24/5-14/5a | | 4.2p+17=3.2p+2 | | 4x^2-13x-116=0 | | -9.2=y+7.7 | | 13.75=0.25+0.50 | | 21.6+4.4t=5.32 | | 5x(-4x+4)=1 | | 18+9p12p-31= | | -13=2.7x-1.35x | | 16.331+m=38.478 | | 9g-47g-3= | | 24577=x-76x | | f(x)=8ln(x) | | 4x+2(7x+11)=112 | | 2b-6b+3= | | 13y-22y=12 | | 1000-1= | | (3+1/3)*(2+1/2)=x | | 10=4y+10+5y | | 4(f-5)-3=2f-3 | | (3+1/3)x(2+1/2)=x | | 35.7/5.24= | | (1-y)(3y+7)=0 | | (19b-6)-6(3b+2)=-2 | | 32x^2+40X-2016=0 | | 3p+2110p= | | h-79=83 | | 3w2w+6= | | (3x+5)-(9x-4)= | | p-0.20p=5 | | 2(1a+2a)= | | (8x+7)-(9x-8)= |

Equations solver categories